On Multiple Hypotheses LAO Testing With Rejection of Decision for Two Dependent Objects - Evgueni Haroutunian; Aram Yessayan; Narine Harutyunyan (Изд-во НАН РА)
Multiple statistical hypotheses testing with possibility of rejecting of decision is considered for model consisting of two dependent objects characterized by joint discrete probability distribution. The matrix of error probabilities exponents (reliabilities) of asymptotically optimal tests is studied.
Keywords: Mathematics; Algorithm